Enhancing Business Communication Skills in Vocational Education: A Generative Ai Approach for Personalized Learning - Wijayati, Titik; Safitri, Yulita Dwi; Hayatie, Marliza Noor (Frontier Management Science, 2024)
In the realm of higher education, there is an increasing emphasis on holistic education approaches that extend beyond academic achievements to encompass various dimensions of student well-being, including social, ethical, spiritual, civic, intellectual, and physical health. This paper explores the growing intersection between student mental health and generative artificial intelligence (AI), examining the potential of AI to enhance holistic education by providing personalized mental health support. The study highlights the eco-holistic model's advocacy for a "whole school" approach, which integrates mental, physical, social, emotional, and environmental aspects to improve student well-being. Additionally, the paper discusses the role of generative AI in addressing student mental health issues, offering innovative solutions such as AI-powered chatbots for real-time support, virtual therapy sessions, and the early identification of at-risk students. Ethical considerations, including privacy, data security, and the need for ongoing research, are also examined. The findings underscore the potential of AI to transform mental health support in higher education, making it more accessible and personalized, thus contributing to the overall well-being and success of students.